2015
DOI: 10.1017/s0033291714003067
|View full text |Cite
|
Sign up to set email alerts
|

The similarity of the structure of DSM-IV criteria for major depression in depressed women from China, the United States and Europe

Abstract: BackgroundDo DSM-IV diagnostic criteria for major depression (MD) in Chinese and Western women perform in a similar manner?MethodThe CONVERGE study included interview-based assessments of women of Han Chinese descent with treated recurrent MD. Using Mplus software, we investigated the overall degree of between-sample measurement invariance (MI) for DSM-IV diagnostic criteria for MD in the CONVERGE sample and samples selected from four major Western studies from the USA and Europe matched to the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
5
15
0
Order By: Relevance
“…The CONVERGE sample may be imperfectly representative of MD and the anxiety disorders. Results from CONVERGE have been largely consistent with MD results from other populations, however 26, 27 , so the present analysis is expected to be generalizable to MD and comorbid anxiety disorders in other populations. The logistic regressions were unadjusted for demographic characteristics, but since the sample is largely homogenous (same ethnicity, same sex, and relatively limited age range), it’s probable that this biased the estimates minimally.…”
Section: Discussionsupporting
confidence: 69%
“…The CONVERGE sample may be imperfectly representative of MD and the anxiety disorders. Results from CONVERGE have been largely consistent with MD results from other populations, however 26, 27 , so the present analysis is expected to be generalizable to MD and comorbid anxiety disorders in other populations. The logistic regressions were unadjusted for demographic characteristics, but since the sample is largely homogenous (same ethnicity, same sex, and relatively limited age range), it’s probable that this biased the estimates minimally.…”
Section: Discussionsupporting
confidence: 69%
“…40 Previous research on structural invariance of MD measurement has been reported elsewhere, indicating that the DSM criteria perform similarly in this sample relative to European and U.S. samples. 41 Representativeness of the sample with regard to severity, chronicity, and number of depressive episodes has also been reported previously, and the mean illness duration of this sample was 9.75 years. 42 …”
Section: Methodssupporting
confidence: 74%
“…Diagnoses of depressive disorders were completed using the (Kendler et al, 2015). Representativeness of the sample with regard to severity, chronicity, and number of depressive episodes has also been reported previously, and the mean illness duration of this sample was 9.75 years (Li et al, 2012).…”
Section: Sample Ascertainmentmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous research on structural invariance of MDD measurement has been reported elsewhere, indicating that the DSM criteria perform similarly in this sample relative to European and U.S. samples (Kendler et al 2015). …”
Section: Methodsmentioning
confidence: 51%